Visual Aesthetics of the Suzzanna: Malam Jumat Kliwon Movie Posters from 1986 and 2023 - Prasetyo, Martinus Eko; Ahmad, Asrullah (DeKaVe, 2024)
The horror film titled Suzzanna: Malam Jumat Kliwon is one of the legendary horror films that is full of nostalgia and loved by horror movie enthusiasts in Indonesia. The success of this film is undoubtedly linked to one of its promotional media, which emerged as an information medium announcing the film's release. Promotional media, which originally took the form of conventional film poster designs, continues to be a mainstay in promoting the release of a film by introducing the main characters, film title, and schedule, all packaged aesthetically in visually appealing posters. This research discusses the importance of the film posters for Suzzanna: Malam Jumat Kliwon, created in 1986 and 2023. From this, the fundamental differences between the two can be identified in terms of visual design aesthetics through the theoretical principles of visual communication design, covering typography, layout, color, point of interest, and design styles used. This research uses a descriptive qualitative approach, directly analyzing the horror film posters from 1986 and 2023 of the film Suzzanna: Malam Jumat Kliwon, supplemented by supporting journals and a literature review. The study reveals the differences in poster design styles over these two different periods.